Distress and Positive Experiences Among Adolescents in Northern Chile in the Context of the COVID-19 Pandemic: A Qualitative Study - Katherin Castillo-Morales; Ricardo Espinoza-Tapia; Diego Portilla-Saavedra; Rodrigo Moya-Vergara (Societies)
The COVID-19 pandemic and the confinement measures adopted by most countries have impacted global mental health, with particular interest in the effects on adolescents due to the tension between lockdown measures and the challenges of their developmental stage. Therefore, this study examined the distress and positive experiences reported by adolescents in northern Chile during the pandemic. A comprehensive study was conducted among adolescents in northern Chile. Discussion groups were utilized to investigate their experiences during the pandemic. The discussions were transcribed, and their content was analyzed by thematic analysis to create emerging categories and subcategories. Eleven discussion groups were conducted with a total of 51 adolescents. The findings were organized into two categories: distress and positive experiences during the pandemic. The distress experiences category included experiences related to confinement, educational tensions, risk of contagion, being an adolescent, and anxious–depressive emotions and symptoms. Meanwhile, the positive experiences category highlighted experiences related to interpersonal relationships through social networks, hobbies, activism, and pets. This research provides guiding results for policymakers and mental health authorities to incorporate this information when creating initiatives for working with the adolescent population. It considers the impact on them, but also incorporates the reported positive experiences as coping mechanisms for other difficulties.